Determination of The Best Concentration of Chitosan as a Recirculation Filter for Growth and Survival of Tilapia (Oreochromis niloticus) - Miska Sanda Lembang; Widiawati Widiawati (Journal of Aquaculture and Fish Health, 2022)
Tilapia (Oreochromis niloticus) is a cultivated commodity that is widely developed because of its economic value and high nutritional content. However, in aquaculture activities, problems such as water pollution reduce water quality. This problem means continuous water changes to maintain water quality. A recirculation system can be a solution by reusing water. The use of filters is an important factor in a recirculation system. One alternative filter is chitosan derived from crab and shrimp shell waste. This study aims to determine the optimal concentration of chitosan as a recirculation filter. The study was conducted experimentally using a completely randomized design with four treatments and three replications. Each treatment is a variation of the concentration of chitosan as a filter. Analysis of measurements carried out was absolute weight growth, specific growth rate, survival, and water quality. Based on the ANOVA results, each treatment had a significant effect on the absolute weight growth of tilapia, P<0.05, with P3 being the most significantly different. At the same time, the specific growth rate and survival of tilapia did not significantly affect P>0.05. The water quality measurements showed that the temperature, pH, ammonia, and DO values ​​were still by the quality standards of tilapia aquaculture, with P3 treatment, which gave better water quality results. Based on the study results, the optimal concentration of chitosan as a filter in supporting tilapia growth was in the P3 treatment, which was 50 mg.